Predictive Variables Derived From Panoramic Radiographs For Impacted Maxillary Cuspids Treated With Easy Cuspid System. Issue 3 (May 2015) - Caprioglio, Alberto; Finazzi, Francesca; Mortellaro, Carmen; Mangano, Carlo; Lucchina, Alberta Greco; Mangano, Francesco; Levrini, Luca
<x xml:space="preserve">Abstract</x> Abstract The aim of the current study was to find, by means of panoramic radiographs, a viable statistical method to forecast the duration of orthodontic traction of impacted maxillary cuspids. The treatment sample consisted of 51 palatal impacted cuspids (19 unilateral and 32 bilateral) in 35 patients (aged between 10.5 and 17.5 y) with a cervical vertebral maturation between cervical stage 1 and 4. Each patient underwent the same combined surgical-orthodontic technique. Anamnestic data as well as pretreatment panoramic radiograph and cephalogram with European Board of Orthodontics analysis were recorded for each case. Eight radiographic indicators were derived from panoramic films to define the reliable position of the impacted cuspid. Multiple regression analysis was used. All cuspids were successfully treated with an average traction time of 99 days (range, 33–188 d). The pretreatment radiographic features assessed on the panoramic radiographs did not significantly affect the duration of traction. The formula based on α angle, d1 distance, and S sector forecasted an average traction time of 123 days (range, 63–210 d), which is longer than the real time. No relevant correlations were found between orthodontic traction time and pretreatment radiograph parameters derived from panoramic film at the beginning of the treatment. The classic formula elaborated by Crescini could not be applied to the patients of this study, who were treated with the Easy Cuspid method.